Speech Accuracy and Reading in Children with Cochlear Implants. - Lucchesi, Fernando Del Mando; Almeida-Verdu, Ana Claudia M.; Bolsoni-Silva, Alessandra Turini; Buffa, Maria José Monteiro Benjamin; das Graças de Souza, Deisy (Psychological Record, 2022)
Research on relations between hearing through cochlear implants and accurate speech is still scarce. The present study used the stimulus equivalence paradigm to investigate the effects of systematically teaching reading skills on speech accuracy in four children with cochlear implants. We used 17 sets of stimuli, each with three dictated (A) and printed (C) words, corresponding pictures (B), and dictated and printed syllables from each word (As and Cs). After teaching stimulus–stimulus relations (AB, AC, and AsCs) and stimulus–response relations (i.e., constructed responses under the control of printed words [CE]), we measured emergent relations, including picture naming (BD) and word reading (CD). Word reading and picture naming were systematically evaluated across stimulus sets (units) according to a single-subject experimental design. All four children presented improvements in reading and speech accuracy in the picture-naming tasks. These results suggest that exposing children with cochlear implants to equivalence-based instructional programs can improve speech accuracy in picture naming in this population through the transfer of stimulus control from printed words to pictures.